2008
DOI: 10.1002/dac.936
|View full text |Cite
|
Sign up to set email alerts
|

On the error probability of quasi‐orthogonal space–time block codes

Abstract: SUMMARYIn this paper, we derive the exact pairwise error probabilities (PEPs) of various quasi-orthogonal spacetime block codes (QO-STBCs) using the moment generating function. By classifying the exact PEPs of QO-STBCs into three types, we derive the closed-form expression for each type of PEP. Based on these closed-form expressions, we obtain the union bounds on the symbol error probability and bit error probability for QPSK modulation. Through simulation, it is shown that these union bounds are quite tight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…QOSTBCs have been introduced in as new subclass of LD‐STBCs which keeps full rate but reduces diversity. Indeed, the QOSTBC has higher computational complexity than OSTBC . The following example gives the encoding matrix of a QOSTBC for four transmit antennas: S=()centerx1x2x3x4centerx2*x1*x4*x3*centerx3*x4*x1*x2*centerx4x3x2x1 and its dispersion matrices are given by: leftA1=centercenter1center0center0center0center0center0center0center0center0center0center0center0center0center0center0center1,A2=centercenter0center1center0center0center0center0center0center0center0center0center0center0center0center0center1center0,A3=centercenter0center0center1center0center0center0center0center0center0center0center0center0center0…”
Section: Overview Of Ld‐stbcsmentioning
confidence: 99%
See 2 more Smart Citations
“…QOSTBCs have been introduced in as new subclass of LD‐STBCs which keeps full rate but reduces diversity. Indeed, the QOSTBC has higher computational complexity than OSTBC . The following example gives the encoding matrix of a QOSTBC for four transmit antennas: S=()centerx1x2x3x4centerx2*x1*x4*x3*centerx3*x4*x1*x2*centerx4x3x2x1 and its dispersion matrices are given by: leftA1=centercenter1center0center0center0center0center0center0center0center0center0center0center0center0center0center0center1,A2=centercenter0center1center0center0center0center0center0center0center0center0center0center0center0center0center1center0,A3=centercenter0center0center1center0center0center0center0center0center0center0center0center0center0…”
Section: Overview Of Ld‐stbcsmentioning
confidence: 99%
“…Equations (28), (30), (31), and (32) into (26) give the WLMMSE channel estimator in the general case which suppose that the transmitted signals are selected from improper constellation.…”
Section: Wlmmse Channel Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a type of space-time coding which combines transmit diversity with coding schemes has been proposed to mitigate the Rayleigh fading effects. STBC systems with more than two transmit antennas were studied in [7][8][9][10]. Later, Alamouti [5] presented the space-time block code (STBC) scheme which equips two antennas with space-time coding at the transmitter and intelligent signal processing at the receiver.…”
Section: Introductionmentioning
confidence: 99%
“…The orthogonal structure of STBC was developed in [6]. STBC systems with more than two transmit antennas were studied in [7][8][9][10].The application of STBC schemes to MC-CDMA systems was presented in [11]. Their study demonstrated that space-time coded MC-CDMA systems gain significant profit in transmit diversity in a multipath fading channel.…”
mentioning
confidence: 99%